Becoming Women : The Embodied Self in Image Culture - Rice, Carla (Book collections on Project MUSE., 2014)
In a culture where beauty is currency, women's bodies are often perceived as measures of value and worth. The search for visibility and self-acceptance can be daunting, especially for those on the cultural margins of "beauty."Becoming Women offers a thoughtful examination of the search for identity in an image-oriented world. That search is told through the experiences of a group of women who came of age in the wake of second and third wave feminism, featuring voices from marginalized and misrepresented groups. Carla Rice pairs popular imagery with personal narratives to expose the "culture of contradiction" where increases in individual body acceptance have been matched by even more restrictive feminine image ideals and norms. With insider insights from the Dove Campaign for Real Beauty, Rice exposes the beauty industry's colonization of women's bodies, and examines why "the beauty myth" has yet to be resolved